The golden ark: arsenopyrite crystal plasticity and the retention of gold through high strain and metamorphism. (21st March 2016) - Fougerouse, Denis; Micklethwaite, Steven; Halfpenny, Angela; Reddy, Steven M.; Cliff, John B.; Martin, Laure A. J.; Kilburn, Matt; Guagliardo, Paul; Ulrich, Stanislav
Abstract: Quantitative electron backscatter diffraction analysis and ion microprobe imaging of gold‐rich arsenopyrites provide the first insights into the crystal plasticity and element mobility behaviour of arsenopyrites through metamorphism (340°–460° and 2 kbar). Remarkably, the gold‐rich arsenopyrites remained structurally and chemically robust during high strain deformation. It was only during a superimposed lower strain deformation event, at a high angle to the preferred orientation of the arsenopyrites, that small amounts of crystal plasticity affected the arsenopyrites. During the low strain event, a dissolution–reprecipitation reaction resulted in loss of gold from the crystal lattice, facilitated by localised domains of recrystallisation, most likely due to fluid percolation along sub‐ and new grain boundaries. We suggest that the abundance and rheologically robust nature of gold‐rich arsenopyrite in giant gold deposits, affected by greenschist–amphibolite metamorphism, is actually critical in the preservation of those deposits.